Leg stiffness in walking and running - Lipfert, S.; Seyfarth, A.; Blickhan, R. (ISB Congress, 2006)
Aims of this study were a) calculating the correlation coefficients of leg stiffness in running and walking, and b) comparing leg stiffness of both gaits. We hypothesized that vertical ground reaction forces (GRFs) and displacement of the center of mass (CoM) would correlate significantly in a positive linear way for running as well as for walking. It was also hypothesized no significant intra- or inter-individual differences for leg stiffness.